Aprendizagem cooperativa apoiada por realidade aumentada no ensino de química - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The present work aims to analyze cooperative learning supported by Augmented Reality as aid of Chemistry Teaching from an approach in Organic Compound Reactions. To achieve the objectives, a case study was used in order to verify the benefits that AR will bring to education. From this, an Augmented Reality application was developed using the Jigsaw I technique that allowed the study in groups with joint interactions between teacher and student. It also allowed the student to visualize in three dimensions the organic reactions through mobile devices and markers. The group studies allowed the interactions with resulting cognitive aspects, with this, it was worked from Vygotsky's concepts about the Proximal Development Zone PDZ. The presentation and use of this study provided the teacher and student with the ability to experience a new way of teaching and learning, with benefits in school performance. We believe that an integrated way of approaching science teaching, in which Chemistry dialogues with the teacher, student and learning mediator, helps to provide the student with the construction of a concise chemical thought that branches into later grades. With this study it was possible to initially verify that 31.4% of the students had a lower than expected income, at the end of the experiment it decreased to 9.2%, so the recovery for acceptable income was to 22.2% who were able to recover. In the experiment, 60% of the cooperative learning groups achieved higher income than other learning groups. This result highlights the importance of working with these learning perspectives, uniting work in cooperative groups and attractive technologies that can collaborate effectively to build knowledge in school disciplines.
Cooperative learning supported by augmented reality in chemistry teaching
Keywords: Ensino de Química; Reações de Compostos Orgânicos; Cooperative Learning; Zona de Desenvolvimento Proximal; Processo de aprendizagem; CIÊNCIAS EXATAS E DA TERRA; Aprendizagem Cooperativa; Realidade Aumentada; Química